A 14-bit 5MS/s SAR ADC with digital calibration algorithm for OLED display touch system. (September 2022) - Wu, Si; Guo, Xiaoyu; Li, Hongge; Xia, Tongsheng
Abstract: In this article, we propose a 14-bit successive approximation register (SAR) analog-to-digital converter (ADC) based on digital calibration algorithm for large-size organic light-emitting diode (OLED) display touch chip. The SAR ADC uses a digital-to-analog convertor (DAC) segmented into two sub-DACs in each channel. A total of two channels are used in the ADC to realize interleaved sampling. The proposed digital calibration technique improves the spurious free dynamic range (SFDR) over 30 dB and reduces the integrated non-linearity (INL) over ten times with different capacitive DAC mismatches. The peaks of differential non-linearity (DNL) and INL are measured to be 0.520 LSB and 1.027 LSB, respectively. The 14 bit 5 MS/s ADC achieves an ENOB of 12.4, a power consumption of 1.054 mW by 110-nm CMOS process, and leads to a figure of merit (FoM) of 14.08 fJ/conv.-step. Highlights: A novel SAR ADC based on digital calibration algorithm for large-size OLED display touch system is proposed to improve the SFDR over 30 dB. The proposed SAR ADC uses a DAC segmented into two sub-DACs in each column and a total of two channels are used to realize interleaved sampling and self calibration. The proposed digital calibration can be carried out all the time during conversion of ADC to calibrate the weight error and deviation of SAR ADC.